The Malaysian AEC professionals work culture could improve organizational team productivity during industrialized project delivery - Abdul Ghafar, Maszura; Ibrahim, Rahinah (Universiti Putra Malaysia Press, 2018)
There is miscoordination in Malaysian construction project delivery resulting in many variation orders (v/o) in the industry. Hence, the Construction Industry Transformation Program 2016-2025 (CITP) is developed to facilitate the future of Malaysian construction industry. This paper presents the results of study on factors in Malaysian architecture-engineering-contractor (AEC) professionals work culture that could improve Malaysian organizational team productivity during industrialized project delivery. This is a case study involving observation and interviews of 14 participants in a Malaysian organization to identify the cultural criteria for successful AEC collaboration. The investigation covers work culture preferences, the inflows and outflows of tacit knowledge through interdependent tasks, and the collaboration processes and related technologies used. Results indicate that four operating characteristics occur in Malaysian building projects. Integration of culture knowledge with Building Information Modeling (BIM) in projects could alleviate better productivity. Finally, this study recommends potential work culture criteria that could uplift Malaysian AEC technology, skill, competencies and expertise, and provide higher incomes commensurate to the construction workforce.